European constitutionalism beyond the state - Weiler, Joseph, 1951-; Wind, Marlene, 1963- (Cambridge ; New York : Cambridge University Press, 2003)
Leading scholars of European constitutionalism highlight different facets of the new constitutional discussion. This book delineates new ways of thinking about the future of Europe. This book will appeal to anyone interested in the timely subject of constitutionalism including students and practitioners of law, politics and philosophy.
Cover; Half-title; Title; Copyright; CONTENTS; CONTRIBUTORS; Introduction European constitutionalism beyond the state; 1 In defence of the status quo: Europe's constitutional Sonderweg; 2 Postnational constitutionalism and the problem of translation; 3 The unfinished constitution of the European Union: principles, processes and culture; 4 Europe and the constitution: what if this is as good as it gets?; 5 The European Union as a polycentric polity: returning to a neo-medieval Europe?; 6 Beyond representative democracy: constitutionalism in a polycentric polity.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Constitutional law -- European Union countries; European Union countries -- Politics and government; Droit constitutionnel -- Pays de l'Union européenne.; Union européenne.; Pays de l'Union européenne -- Politique et gouvernement; LAW -- International; Constitutional law; Politics and government; European Union countries; Aufsatzsammlung; Verfassung; Democratisering; Constitutionalisme; Europese Unie; Pays de l'Union européenne -- Politique et gouvernement; Droit constitutionnel (droit européen); Droit constitutionnel -- Pays de l'Union européenne.; Constitutionnalisme -- Pays de l'Union européenne.; Europäische Union; Electronic books; Electronic books